H2 binding energy may be an auxiliary criterion of H adsorption free energy to estimate hydrogen evolution catalyst - Chao Kong; Yanxia Han; Lijie Hou; Chao Shuai; Ke Gai; Xiaoli Song (Next Energy)
The H adsorption free energy (ΔGH) is commonly used as a descriptor to estimate the activity of hydrogen evolution catalyst and a ΔGH close to zero is desired for the hydrogen evolution catalyst. The whole hydrogen evolution reaction (HER) process includes the generation *H and *H2 and *H2 desorption. However, the value of ΔGH only decides the generation rate of adsorbed H (*H) and H2 (*H2) and is not related with the rate of *H2 desorption. The H2 binding energy (∆EH2) may influence the step of *H2 desorption. Therefore, in this paper, H2 binding energy (∆EH2) and ΔGH on the commonly used HER catalysts were calculated using the density functional theory (DFT) method. The results show that ΔGH is irrelevant to ∆EH2and the excellent HER catalysts such as Pt and [Fe-Fe] hydrogenase have a desired ΔGH and low ∆EH2. The value of ΔGH decides the generation rate of adsorbed H (*H) and H2 (*H2) and the low ∆EH2can promote *H2 desorption from the surface of catalyst. The activity of HER catalyst is codetermined by ΔGH and ∆EH2. Based on the calculations, we firstly propose that ∆EH2 can act as an auxiliary criterion of ΔGH to estimate the activity of HER catalyst.